2009
DOI: 10.1097/hjh.0b013e328330e84d
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on daytime and night-time blood pressure: similarities and differences

Abstract: Objective To examine whether the genetic influences on blood pressure (BP) during night-time are different from those during daytime and the extent to which they depend on ethnicity or sex. Methods Ambulatory BP was measured in 240 European–American and 190 African–American twins (mean ± SD age, 17.2 ± 3.4). Individuals with night-time BP falls more than 10% of the daytime values were defined as dippers. A bivariate analysis of the daytime and the night-time BP levels, as well as a liability-threshold model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 33 publications
6
41
0
Order By: Relevance
“…Although not statistically different in the present study, the heritability estimate for night-time SBP was higher than the heritability estimate for daytime SBP, whereas the heritability estimates for daytime and night-time DBP were very similar in magnitude. It has been suggested that studies investigating the genetics of hypertension using night-time BP may be more powerful than those using daytime BP, as night-time BP is less likely to be influenced by environmental factors [29]. However, studies that have found night-time BP to be more heritable have not examined whether the difference was statistically significant [29].…”
Section: Discussionmentioning
confidence: 99%
“…Although not statistically different in the present study, the heritability estimate for night-time SBP was higher than the heritability estimate for daytime SBP, whereas the heritability estimates for daytime and night-time DBP were very similar in magnitude. It has been suggested that studies investigating the genetics of hypertension using night-time BP may be more powerful than those using daytime BP, as night-time BP is less likely to be influenced by environmental factors [29]. However, studies that have found night-time BP to be more heritable have not examined whether the difference was statistically significant [29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on twins, large cohorts, and isolated pedigrees have provided more insight into understanding complex traits of hypertension compared with case-control association studies (Hiekkalinna et al, 2012;Wang et al, 2011;Wu et al, 2010). In addition, genetic studies using ambulatory blood pressure (BP) measurements as a phenotype were found to be potentially more powerful than those using office BP measured in the clinic (Fava et al, 2004;Kotchen et al, 2000;Kupper et al, 2005;Tomaszewski et al, 2010;Wang et al, 2009). A distinct advantage is that ambulatory recordings allow collection of multiple day and night values in a natural setting.…”
mentioning
confidence: 99%
“…This could be explained, in part, by the fact that night-time BP is less influenced by environmental factors than daytime (and therefore 24-hour) BP, a phenomenon previously reported in studies investigating the genetics of hypertension. 27 It is also possible that the inverse association during daytime is blunted by an acute pressure effect of caffeine intake during the morning. The stronger associations of night-time BP than daytime BP with caffeine is of importance, given the increasing evidence that night-time BP provides the greatest information regarding cariovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…27 It is also possible that the inverse association during daytime is blunted by an acute pressure effect of caffeine intake during the morning. The stronger associations of night-time BP than daytime BP with caffeine is of importance, given the increasing evidence that night-time BP provides the greatest information regarding cariovascular risk.…”
Section: Guessous Et Al Ambulatory Blood Pressure and Urinary Caffeinmentioning
confidence: 99%